Tinjauan Yuridis Pelaku Tindak Pidana Kejahatan Seksual pada Anak dibawah Umur - Putra, Bima Mandala (UM Purwokerto Press, 2024)
The criminal act of sexual violence that often disturbs society is sexual violence against children committed by adults. This is because children are physically weak so it is easier for adults to commit crimes. This research uses a type of normative juridical legal research. The research approach method used in this research is a statutory approach and an analytical approach. In this research, secondary data is used, namely data obtained from library research by collecting legal materials. Conclusions are made deductively, which means drawing conclusions from general things to specific things. Based on the results of research and discussion of the Juridical Review on Punishment for Perpetrators of Sexual Relations with Children, in this case the judge determines whether a person is guilty or not because the judge is God's representative in determining the length of the sentence. guided by the minimum and maximum threat provisions formulated in the law. -invitation. The minimum and maximum criminal threats have been formulated generally in the Criminal Code, while the minimum and maximum criminal threats have been specifically formulated in every law outside the Criminal Code, and the judge's advice in handling cases of criminal sexual violence against children must pay attention to the laws in force in Indonesia , because Indonesia adheres to the Continental European legal system which places legislation as the main source, so that justice can be guaranteed to everyone who comes into contact with the law.